-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy path2020-Solutions.tex
149 lines (116 loc) · 7.81 KB
/
2020-Solutions.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
\documentclass{amsart}
\setlength{\parindent}{0pt}
\setlength{\parskip}{\baselineskip}
\raggedbottom
\begin{document}
\begin{center}
Science Atlantic Math Competition 2020 Solutions
\end{center}
\textbf{Problem 1}\\
Write $\tan(x) + \cot(2x)$ in the form $bf(cx)$, where $b$ and $c$ are real numbers, and $f$ is a standard trigonometric function.
\textit{Solution}\\
\begin{align*}
\tan(x) + \cot(2x) &= \frac{\sin(x)}{\cos(x)} + \frac{\cos(2x)}{\sin(2x)} \\
&= \frac{\sin(x)}{\cos(x)} + \frac{\cos^2(x) - \sin^2(x)}{2\sin(x)\cos(x)} \\
&= \frac{2 \sin^2(x) + \cos^2(x) - \sin^2(x)}{2\sin(x)\cos(x)} \\
&= \frac{\sin^2(x) + \cos^2(x)}{2\sin(x)\cos(x)} \\
&= \frac{1}{\sin(2x)} = \csc(2x)
\end{align*}
\pagebreak
\textbf{Problem 2}\\
A bug located at $(2, 0, 0)$ in $\mathbb{R}^3$ wants to get to $(-2, 0, 0)$ but is impeded by an impenetrable sphere of radius $1$ centred at the origin.
Describe and give the length of the shortest path available to this bug.
\textit{Solution}\\
The projection of a path onto a plane is no longer than the path, so with no loss of generality, model the problem as the shortest path from $(2, 0)$ to $(-2, 0)$ which does not pass through the unit circle.
If a string is stretched from $(2, 0)$ to $(-2, 0)$, its path consists of two line segments from $(-2, 0)$ and $(2, 0)$ meeting the unit circle at the points of tangency and the arc between those points.
The points of tangency lie at $(-1/2, \sqrt{3}/2)$ and $(1/2, \sqrt{3}/2)$, or at angles of $2\pi/3$ and $\pi/3$ on the unit circle, respectively.
The distances from $(-2, 0)$ to $(-1/2, \sqrt{3}/2)$ and from $(2, 0)$ to $(1/2, \sqrt{3}/2)$ are both $\sqrt{3}$, and the length of the arc between $\pi/3$ and $2\pi/3$ is $\pi/3$, so the length of the path is $2\sqrt{3} + \pi/3$.
\pagebreak
\textbf{Problem 3}\\
A tetrahedron has vertices $ABCD$.
Suppose that the plane $\gamma$ bisects the (internal) dihedral angle along edge $AB$ and meets edge $CD$ at $G$.
Prove that
\[ \frac{\lvert ABC \rvert}{\lvert ABD \rvert} = \frac{\lvert CG \rvert}{\lvert GD \rvert} \]
\textit{Solution}\\
\pagebreak
\textbf{Problem 4}\\
A sequence of natural numbers is \textit{eccentric} if no term can be written as a sum of terms that come before it (repetition is allowed).
For instance, the finite sequence $12, 3, 13, 17, 2$ is eccentric, but $11, 3, 13, 17, 2$ is not because $11 + 3 + 3 = 17$.
Does there exist an infinite eccentric sequence?
\textit{Solution}\\
Let $(a_n)_{n = 0}^\infty$ be a sequence of natural numbers.
If any terms are repeated, the sequence is not eccentric (because a single term is considered a sum).
Suppose no terms are repeated.
By the pigeonhole principle, there exists $b$ such that $0 \leq b < a_0$ and infinitely many $a_n \equiv b \pmod{a_0}$.
Then there exists a subsequence $(a_{n_i})_{i = 0}^\infty$ of $(a_n)$ such that each $a_{n_i} \equiv b \pmod{a_0}$.
Then there exists $j$ such that $a_{n_0} = ja_0 + b$.
Since $(a_n)$ has no repetitions, there exists $k \leq j + 1$ such that $a_{n_k} > a_{n_0}$, implying that there exists $\ell > j$ such that $a_{n_i} = \ell a_0 + b$.
Then $a_{n_i} = a_{n_0} + (\ell - j) a_0$, so $(a_n)$ is not eccentric.
Therefore no infinite eccentric sequences exist.
\pagebreak
\textbf{Problem 5}\\
Define a \textit{factorial $M$-partition} of $N$ to be a set $\{a_1, a_2, \cdots, a_M\}$ of positive integers such that $\displaystyle N = \sum_{i = 1}^M a_i!$.
Furthemore, define a factorial $M$-partition to be \textit{proper} if the $a_i$ are all unequal.
Show that if for some $M, N$ there is a proper factorial $M$-partition of $N$, then every other proper factorial $M$-partition of $N$ is a permutation of it.
\textit{Solution}\\
First we show that $1! + \cdots + (n - 1)! < n!$ by induction.
Indeed, $1! < 2!$ and if $n > 1$ and $1 + \cdots + (n - 1)! < n!$, then $1 + \cdots n! < 2n! < (n + 1)n! < (n + 1)!$.
Now we show the main result by induction on $M$.
For $M = 1$, $\{a!\} = \{b!\} \iff a = b$.
Now suppose for a given $M$ that for every $N$ with a proper factorial $M$-partition, $N$ admits only one such partition up to ordering.
Let $N$ be a number with a proper factorial $(M + 1)$-partition.
Let $n$ be the unique natural number such that $n! \leq N < (n + 1)!$.
Since $1! + \cdots + (n - 1)! < n! \leq N$, at least one element of the partition is $\geq n$.
On the other hand, all terms of the partition are $<(n + 1)$ so the largest element is $n$.
Now by supposition, $N - n$ has a unique ordered proper factorial $M$-partition, so appending $n$ to this gives a unique ordered proper factorial $(M + 1)$-partition of $N$.
Therefore the result holds for all $M, N$ by induction.
\pagebreak
\textbf{Problem 6}\\
Show for integers $\geq 1$ that
\[ \frac{d^n}{dx^n} (1 + x)^{n - 1} e^\frac{x}{x + 1} = \frac{e^\frac{x}{x + 1}}{(1 + x)^{n + 1}} \]
\textit{Solution}\\
Let $y = 1 + x$ and note that $\displaystyle (1 + x)^{n - 1} e^\frac{x}{x + 1} = y^{n - 1} e^{1 - \frac{1}{y}}$.
For each $m, n$ let $\displaystyle f_n^{(m)} = \frac{d^m}{dx^m} y^{n - 1} e^{1 - \frac{1}{y}}$.
First we show by induction on $m$ that $f_{(n + 1)}^{(m)} = mf_n^{(m - 1)} + yf_n^{(m)}$.
For the base case $m = 1$, $\displaystyle f_{(n + 1)}^{(1)} = \frac{d}{dx} yf_n = f_n + yf_n^{(1)}$.
For the step case, if $f_{(n + 1)}^{(m)} = mf_n^{(m - 1)} + yf_n^{(m)}$, then $f_{(n + 1)}^{(m + 1)} = mf_n^{(m)} + f_n^{(m)} + yf_n^{(m + 1)} = (m + 1)f_n^{(m)} + yf_n^{(m + 1)}$.
Now we show by induction on $n$ that $f_n^{(n)} = y^{-(n + 1)} e^{1 - \frac{1}{y}}$ as desired.
The base case $n = 0$ is obvious.
For the step case, $f_{(n + 1)}^{(n)} = nf_n^{(n - 1)} + yf_n^{(n)}$ and so $f_{(n + 1)}^{(n + 1)} = nf_n^{(n)} + f_n^{(n)} + yf_n^{(n + 1)} = (n + 1)f_n^{(n)} + yf_n^{(n + 1)}$.
By supposition, $f_n^{(n)} = y^{-(n + 1)} e^{1 - \frac{1}{y}}$ and so $f_n^{(n + 1)} = (-(n + 1)y^{-(n + 2)} + y^{-(n + 3)}) e^{1 - \frac{1}{y}}$.
Substituting, we have $f_{n + 1}^{(n + 1)} = y^{-(n + 2)} e^{1 - \frac{1}{y}}$ as desired.
\pagebreak
\textbf{Problem 7}\\
Assess the convergence of
\[ \sum_{n = 0}^\infty \arctan\left(\frac{2n - 1}{n^4 - 2n^3 + n^2 + 1}\right) \]
If convergent, give the value of the series.
\textit{Solution}\\
By the rule
\[ \displaystyle \tan(x - y) = \frac{\tan(x) - \tan(y)}{1 + \tan(x)\tan(y)} \]
we have that
\[ \displaystyle \arctan\left(\frac{2n - 1}{n^4 - 2n^3 + n^2 + 1}\right) = \arctan\left(\frac{n^2 - (n - 1)^2}{1 + n^2(n - 1)^2}\right) = \arctan(n^2) - \arctan((n - 1)^2) \]
Then
\begin{align*} \sum_{n = 0}^\infty \arctan\left(\frac{2n - 1}{n^4 - 2n^3 + n^2 + 1}\right) &= \sum_{n = 0}^\infty \arctan(n^2) - \arctan((n - 1)^2) \\
&= -\arctan((-1)^2) + \lim_{n \to \infty} \arctan(n^2) \\
&= -\frac{\pi}{4} + \frac{\pi}{2} = \frac{\pi}{4}
\end{align*}
\pagebreak
\textbf{Problem 8}\\
The symmetric $n \times n$ matrix $A_n$ has $ij$-th entry
\[ \begin{cases} (3 - (-1)^i) / 2 & i = j \\ -1 & i = j \pm 1 \\ 0 & \text{otherwise} \end{cases} \]
Determine $\det(A_n)$ for all positive integers $n$.
\textit{Solution}\\
Let $e_i = (3 - (-1)^i)/2$.
An easy calculation shows that $A_1 = [2]$ and $A_2 = \begin{bmatrix} 2 & -1 \\ -1 & 1 \end{bmatrix}$ have determinants 2 and 1 respectively.
In the general case, $A_n$ has $A_{n - 2}$ as the top left $(n - 2) \times (n - 2)$ sub-block and $A_{n - 1}$ as the top left $(n - 1) \times (n - 1)$ sub-block.
\[ \begin{bmatrix}
& & & \cdots & \cdots \\
& A_{n - 2} & & \cdots & \cdots \\
& & & -1 & \cdots \\
\cdots & \cdots & -1 & e_{n - 1} & -1 \\
\cdots & \cdots & \cdots & -1 & e_n
\end{bmatrix} \]
Then $\det(A_n) = e_n \det(A_{n - 1} - \det(A_{n - 2})$ by evaluating first along the $n$-th row, then the $n$-th column of the resulting minors.
This recurrence yields $\det(A_3) = 0$, $\det(A_4) = -1$, $\det(A_5) = -2$, $\det(A_6) = -1$, $\det(A_7) = 0$, $\det(A_8) = 1$, $\det(A_9) = 2$, and $\det(A_{10}) = 1$.
Since $\det(A_9) = \det(A_1)$ and $\det(A_{10}) = \det(A_2)$, the sequence of determinants has period 8 and follows this pattern.
\end{document}